2019
DOI: 10.2298/fil1917589a
|View full text |Cite
|
Sign up to set email alerts
|

Bivariate discrete Nadarajah and Haghighi distribution: Properties and different methods of estimation

Abstract: The exponential distribution is commonly used to model different phenomena in statistics and reliability engineering. A new extension of exponential distribution known as the Nadarajah and Haghighi [An extension of the exponential distribution, Statistics: A Journal of Theoretical and Applied Statistics 45 (2011) 543-558.] distribution was introduced in the literature to accommodate the inflation of zero in the data. In practice, however, discrete data are easy to collect as compared to continuous data. Discre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…., and investigated some mathematical properties. Recently, Ali et al [48] suggested the bivariate discrete NH model and reported some useful mathematical properties along with the estimation of model parameters with the help of seven wellknown methods.…”
Section: Life Testing Under Censoring Schemes Haghighimentioning
confidence: 99%
“…., and investigated some mathematical properties. Recently, Ali et al [48] suggested the bivariate discrete NH model and reported some useful mathematical properties along with the estimation of model parameters with the help of seven wellknown methods.…”
Section: Life Testing Under Censoring Schemes Haghighimentioning
confidence: 99%
“…In 1953, Lehmann, firstly, introduced PHR model in univariate case for testing of hypothesis problem, which named Lemann alternatives. Its dual is called as the proportional reversed hazard rate (PRHR), which proposed by Gupta et al 3 Several methods of bivariate distributions are constructed with its linked copula as Mazo et al, 4 Salleh et al 5 and Sajid et al 6 A new lifetime distribution with three-parameter is proposed by a combination of Rayleigh distribution and extended odd Weibull family to produce the extended odd Weibull Rayleigh with applications of COVID-19 data introduced by Almongy. 7 The PHR model is defined as…”
Section: Introductionmentioning
confidence: 99%
“…Several methods of bivariate distributions are constructed with its linked copula as Mazo et al., 4 Salleh et al 5 . and Sajid et al 6 . A new lifetime distribution with three‐parameter is proposed by a combination of Rayleigh distribution and extended odd Weibull family to produce the extended odd Weibull Rayleigh with applications of COVID‐19 data introduced by Almongy 7 …”
Section: Introductionmentioning
confidence: 99%